Erectile Dysfunction Secondary to Herpes Zoster - Paudel, Vikash (Journal of Nepal Health Research Council, 2020)
Varicella Zoster is dermatomal neuropathic disease caused by reactivation of varicella zoster virus, characterized by vesico-bullous eruptions. The sacral dermatomal involvement in shingles is a rare phenomenon but well recognized cause of urinary retention, bladder dysfunction but rarely erectile dysfunction. We present a case of sacral herpes zoster with erectile dysfunction in a sexually active adult male. Keywords: Erectile Dysfunction; herpes zoster; Nepal.